Effectiveness of “Istami” app in enhancing Arabic listening skills: A study at Ats-Tsamina Lil Ummah, Indonesia - Bahrun, Muhammad Farhan; Bakhiet, Bakrie Muhammad; Chamidah, Dewi (Abjadia : International Journal of Education, 2025)
The use of instructional media is an urgent necessity, especially with the widespread utilization of educational technology and the increasing number of users. This requires effective integration of such media into the learning process within educational institutions. This aligns with what was stated by Asriyliyya and her colleagues, that ineffective implementation of the teaching and learning process results in low effectiveness, reaching only 48%. However, this issue can be addressed by identifying appropriate instructional media for students. Ats-Tsamina Lil Ummah Institute is one of the institutions striving to utilize instructional media, particularly in its Arabic language course programs. Therefore, this study aims to measure the effectiveness of the "Istami’" application as a listening instructional tool for beginners in the Arabic language course at Ats-Tsamina Lil Ummah Institute in Bogor. The researcher employed an experimental research method with a quantitative approach. The effectiveness of the "Istami’" application was measured using a pretest-posttest design, specifically the one-group pretest-posttest design method. A t-test was used to compare students' pretest and posttest results to determine the application’s effectiveness in teaching listening skills. The research findings show that the "Istami’" application is effective in teaching listening skills. After being implemented in the beginner-level Arabic course at Ats-Tsamina Lil Ummah Institute, statistical analysis revealed that the probability value was lower than the level of significance (0.05 ≥ 0.00). The conclusion of this study emphasizes that technology-based instructional media have a positive impact on the learning process, enhance students’ language proficiency, and improve their academic performance.